2017
DOI: 10.3389/fpsyg.2017.00350
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Leisure and Work Contexts: The Roles of Perceived Enjoyment and Perceived Usefulness in Predicting Mobile Video Calling Use Acceptance

Abstract: There is a rapidly growing body of literature on mobile video calling, which is a promising communication technology; however, little research has focused on user acceptance of mobile video calling, especially in different use contexts. This study explored factors (especially perceived enjoyment) influencing the intention of users to employ video calling in different contexts (a work and a leisure context) by applying the technology acceptance model (TAM) combined with the theory of planned behavior. The revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 75 publications
2
27
0
4
Order By: Relevance
“…HM is regarded as fun derived from using a system like smartphone banking and which triggers more usage. However, the benefits which the users get from using the system may be instrumental to trigger the fun (Pagani, 2004; Salimon et al, 2017) and which implies that bankers must start thinking in this direction by ensuring that the smartphone banking apps are embedded with value‐added functions that can provide customers with a more affective, entertaining and enjoyable experience (Zhou & Feng, 2017). Additionally, the significant and positive relationship between PEoU and SMBU (H3) suggests that smartphone banking users give preference to ease of use of the system against any tasks or functionality that can make life difficult for them.…”
Section: Discussionmentioning
confidence: 99%
“…HM is regarded as fun derived from using a system like smartphone banking and which triggers more usage. However, the benefits which the users get from using the system may be instrumental to trigger the fun (Pagani, 2004; Salimon et al, 2017) and which implies that bankers must start thinking in this direction by ensuring that the smartphone banking apps are embedded with value‐added functions that can provide customers with a more affective, entertaining and enjoyable experience (Zhou & Feng, 2017). Additionally, the significant and positive relationship between PEoU and SMBU (H3) suggests that smartphone banking users give preference to ease of use of the system against any tasks or functionality that can make life difficult for them.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the discriminant validity determined whether the latent variables were distinct factors from one another. As shown in Table 2, the questionnaire items had high levels of convergent validity because the factor loadings were all higher than 0.55 (e.g., Zhou and Feng 2017). In addition, the average variance extracted (AVE) values, which had to be 0.50 or greater (e.g., Lee 2019), indicated that the scales had good convergent validity.…”
Section: Reliability and Validity Testsmentioning
confidence: 99%
“…According to previous studies (e.g., Fornell and Larcker 1981;Zhou and Feng 2017), if the value of squared multiple correlation (SMC) is above 0.50 and the composite reliability (CR) value is above 0.70, then the reliability is acceptable. Table 2 shows that the SMCs of the items were all higher than the criterion (0.50) and that the CR values for all the constructs were above the recommended level of 0.70.…”
Section: Reliability and Validity Testsmentioning
confidence: 99%
“…In the context of social commerce platforms (SCP), Xiang et al [11] mentioned that the more useful a social commerce platform is perceived to be, the more enjoyable it is to use. Zhou and Feng [72] mentioned that perceived usefulness would have a positive influence on the perceived enjoyment of video calling usage. Besides, Demirci et al [73], Parboteeah et al [7,74], Terzis et al [61], and Zheng et al [53] also mentioned that positive cognitive reactions are capable of increasing the emotional part of impulse buying.…”
Section: Relationship Between Perceived Usefulness and Perceived Enjomentioning
confidence: 99%